2020
DOI: 10.1016/j.bja.2020.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Brachial plexus block with ultrasound guidance for upper-limb trauma surgery in children: a retrospective cohort study of 565 cases

Abstract: Background: Upper-limb trauma is a common indication for surgery in children, and general anaesthesia remains the method of choice for these procedures, even though suitable techniques of brachial plexus block are available and fast provision of regional anaesthesia offers a number of distinct advantages. Methods: A retrospective analysis was performed of the data of a large cohort of children undergoing ultrasound-guided brachial plexus blocks during a 4-yr period at a major trauma centre with a catchment are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 32 publications
1
21
0
3
Order By: Relevance
“…This gave rise to an accompanying editorial 12 that questioned the wisdom of adopting this practice by the general anaesthetist without the special skills that the Viennese group possesses. Although the target group of patients is different in the study by Zapradil and colleagues, 8 the same issue is still relevant. Thus, before adopting this approach one should predefine how much supplementation with other drugs is acceptable and when, for the sake of safety, one should convert to proper general anaesthesia.…”
Section: What Is the Need For Conversion To General Anaesthesia (Failure Rate)?mentioning
confidence: 98%
See 3 more Smart Citations
“…This gave rise to an accompanying editorial 12 that questioned the wisdom of adopting this practice by the general anaesthetist without the special skills that the Viennese group possesses. Although the target group of patients is different in the study by Zapradil and colleagues, 8 the same issue is still relevant. Thus, before adopting this approach one should predefine how much supplementation with other drugs is acceptable and when, for the sake of safety, one should convert to proper general anaesthesia.…”
Section: What Is the Need For Conversion To General Anaesthesia (Failure Rate)?mentioning
confidence: 98%
“…Support for this has recently been presented in the Europewide APRICOT study that showed that paediatric regional anaesthesia is still not as widespread as it deserves to be across Europe. 10 Premedication or light sedation vs deep sedation for regional block placement Zadrazil and colleagues 8 strictly labelled blocks that only needed one supplemental dose of i.v. fentanyl as block failures.…”
Section: What Is the Need For Conversion To General Anaesthesia (Failure Rate)?mentioning
confidence: 99%
See 2 more Smart Citations
“…Fully effective anesthesia and analgesia are an important part of fracture treatment. Brachial plexus block (BCB) has a long history of being used for anesthesia and postoperative analgesia in upper limb surgery [4,5]. There are four frequently used approaches for brachial plexus block: intermuscular groove approach, supraclavicular approach, subclavian approach and axillary approach [6,7].…”
Section: Introductionmentioning
confidence: 99%